2015
DOI: 10.4269/ajtmh.14-0373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Patients with Acute Febrile Illnesses and Positive Dengue NS1 Tests in a Tertiary Hospital in Papua New Guinea

Abstract: Abstract. Because the prevalence of dengue fever in urban settings in Papua New Guinea is unknown, we investigated the presence of dengue using the NS1 antigen test in an outpatient-based prospective observational study at Port Moresby General Hospital. Of 140 patients with acute febrile illnesses, dengue fever was diagnosed in 14.9% (20 of 134; 95% confidence interval [95% CI] = 9.6-22.4). Malaria (2 of 137; 1.5%; 95% CI = 0.3-5.7), chikungunya (3 of 140; 2.1%; 95% CI = 0.6-6.6), and bacterial bloodstream inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…To date, only serological studies have provided evidence suggesting continual DENV transmission exists in PNG. 20 , 45 , 46 The molecular data we present here are also limited by the periodical sampling of DENV strains imported into Australia from PNG. However, molecular assessment of circulating DENV strains is essential to understanding genetic diversity, transmission dynamics and disease risks within PNG.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only serological studies have provided evidence suggesting continual DENV transmission exists in PNG. 20 , 45 , 46 The molecular data we present here are also limited by the periodical sampling of DENV strains imported into Australia from PNG. However, molecular assessment of circulating DENV strains is essential to understanding genetic diversity, transmission dynamics and disease risks within PNG.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Papua New Guinea, a study of AFI reported dengue in 14.9%, malaria in 1.5% cases, and chikungunya in 2.1% cases. 13 On the other hand, a study in Indonesia, found the aetiologies of AFI to be typhoid (18%), pneumonia (13%), leptospirosis (12%), urinary tract infections (9%), rickettsioses (8.4%), dengue (7.5%), and meningitis/encephalitis (6.6%). 14 The occurrence of a headache in Scrub Typhus was statistically higher (p=0.028) when compared to other causes.…”
Section: Discussionmentioning
confidence: 98%